Bilad Al-Sham in the memoirs of Muhammad Al-Senussi the Hejaz journey in 1300AH/1883AD - عثمان, ربيع (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Muhammad Al-Senussi is considered one of senior graduates of Al- Zaytoonah and He is one of the first Arab thinkers who called for study of modern sciences' and adopting the reasons for progress in order to restore the Arab and Islamic nation to its status and pride , and it is one most prominent Tunisian officials who worked in the government of Khair al-Din al-Tunisi, which sought to establish a series of reform works adimed at saving Tunisia from its financial crisis and removing foreign influence from it , but the efforts of the Tunisian government failed in the end and Tunisia was subjected to Tunisian protection in the year 1298AH/1881AD , so a large number of Tunisian politicians and intellectuals who rejected the French protection were forced to leave Tunisia , among Senussi who was forced to leave his country as a result of being subjected to severe pressure from the French authorities, so he invoked his desire to perform the rituals of Hajj , he accompanied the Shmi Hajj convoy to Damascus, then moved to Beirut and recorded the details of that trip in his book Hijaz Trip , provided a lot of information related to political , economic , social , cultural and urban conditions in levant in the year 1300AH/1883AD .